Silica-modified monodisperse hexagonal lanthanide nanocrystals: synthesis and biological properties - Kostiv, U; Janoušková, O; Šlouf, M; Kotov, N; Engstová, H; Smolková, K; Ježek, P; Horák, D (Nanoscale, 2015)
Oleic acid-stabilized hexagonal NaYF4:Yb(3+)/Er(3+) nanocrystals, emitting green and red luminescence, were prepared by the high-temperature co-precipitation of lanthanide chlorides. By varying the reaction time and the Ln(3+)/Na(+) ratio, the nanocrystal size can be controlled within the range 16-270 nm. The maximum upconversion quantum yield is achieved under 970 nm excitation. The reverse microemulsion technique using hydrolysis and condensation of tetraethoxysilane is a suitable method to coat the nanocrystal surface with a silica shell to make the particles dispersible and colloidally stable in aqueous media. During the subsequent functionalization, (3-aminopropyl)trimethoxysilane introduced amino groups onto the silica to enable future bioconjugation with the target molecules. All specimens were characterized by TEM microscopy, electron and X-ray diffraction, ATR FT-IR spectroscopy, and upconversion luminescence. Finally, in vitro cytotoxicity and intracellular nanoparticle uptake (using confocal microscopy) were determined with human cervical carcinoma HeLa and mRoGFP HeLa cells, respectively. From the investigated particles, amino-functionalized NaYF4:Yb(3+)/Er(3+) nanocrystals internalized into the cells most efficiently. The nanoparticles proved to be nontoxic at moderate concentrations, which is important when considering their prospective application in biolabeling and luminescence imaging of various cell types.
Keywords: lanthanoidy; HeLa Cells; oxid křemičitý; fluorescenční mikroskopie; Humans; Silicon Dioxide; Microscopy, Fluorescence; Lanthanoid Series Elements; Nanoparticles; HeLa buňky; lidé; nanočástice